Anticancer potential of eugenol in hepatocellular carcinoma through modulation of oxidative stress, inflammation, apoptosis, and proliferation mechanisms - Mohamed Y. Zaky; Hadeer M. Morsy; Adel Abdel-Moneim; Khairy M. A. Zoheir; Anthony Bragoli; Mostafa A. Abdel-Maksoud; Abdulaziz Alamri; Osama M. Ahmed (Discover Oncology)
Abstract This investigation explored the chemopreventive effects of eugenol on diethylnitrosamine (DENA) and acetylaminofluorene (AAF)-induced hepatocellular carcinoma (HCC) in Wistar rats. To induce HCC, DENA was administered intraperitoneally once per week for two weeks at a concentration of 150 mg/kg body weight (b.w.), followed by oral AAF administration for 3 weeks, four times a week, at a dosage of 20 mg/kg b.w. After these three weeks, the rats were treated with eugenol every other day for 17 weeks at a dosage of 20 mg/kg b.w. In vitro, eugenol reduced cell viability (IC50 of 189.29 µg/mL) and inhibited cell migration in the HCC cell line HepG2. Moreover, eugenol treatment in DENA/AAF-induced rats significantly improved cancerous histopathological changes and reduced inflammatory cell infiltration in the liver. Eugenol treatment significantly reduced the activity levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP), along with the levels of total bilirubin (TBIL), alpha-fetoprotein (AFP), carcinoembryonic antigen (CEA), carbohydrate antigen 19–9 (CA 19–9), lipid peroxides (LPO), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β). Additionally, the expressions of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), interleukin-8, C-X-C Motif Chemokine Receptor 3 (CXCR3), B-cell lymphoma 2 (Bcl-2), IQ Motif Containing GTPase Activating Protein 1 (IQGAP1), IQ Motif Containing GTPase Activating Protein 3 (IQGAP3), Harvey rat sarcoma viral oncogene homolog (HRAS), Kirsten rat sarcoma viral oncogene homolog (KRAS), and Ki-67 were downregulated following eugenol administration in DENA/AAF-induced HCC. Conversely, eugenol supplementation significantly enhanced glutathione (GSH) content, as well as the activities of glutathione peroxidase (GPx) and superoxide dismutase (SOD), and the levels of nuclear factor erythroid 2-related factor 2 (Nrf2). Furthermore, the expressions of tumor suppressor gene p53, Bcl-2-associated X protein (BAX), death receptor 4 (DR4), death receptor 5 (DR5), decoy receptor 1 (DcR1), programmed cell death 5 (PDCD5), and IQ Motif Containing GTPase Activating Protein 2 (IQGAP2) were markedly upregulated compared to the DENA/AAF-administered group. These findings indicate that the potent anticancer effects of eugenol are primarily driven by its ability to reduce oxidative stress, suppress inflammation, and inhibit cell proliferation while promoting apoptosis. This study underscores the potential of eugenol as a promising therapeutic agent for the prevention and management of HCC, offering a novel approach to HCC treatment.